Enhancing Tourists’ Satisfaction Through Blockchain Technology ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Blockchain technology, a decentralized ledger system, offers a secure and transparent means to record  transactions, holding promise for enhancing tourists' contentment within the travel industry. Objective: The aim  of the study was to assess how blockchain technology impacts tourists' trust, willingness to pay, and environmental  considerations. Methodology: Employing a qualitative research approach combined with thematic analysis, the study  was conducted. The research was conducted in the Kolkata region of West Bengal. Sample size was 18 participants  who were tourists utilizing travel agency services for travel purposes. Data was collected by semi-structured interview.  Thematic was utilized to analyze the interview data. Results: The research unveiled that respondent possessed a solid  comprehension of blockchain technology and recognized its potential effects on the travel sector. Their preference  leaned towards travel-related products and services utilizing blockchain, driven by the belief in heightened security,  efficiency, and cost-effectiveness. Furthermore, respondents expressed a willingness to invest more in travel offerings  incorporating blockchain technology, assuming it would deliver superior security, transparency, efficiency, sustainability,  and innovation. Conclusion: The study's outcomes affirm that blockchain technology holds the potential to significantly  enhance tourists' satisfaction within the travel industry. Nonetheless, further investigation is required to explore the  precise mechanisms by which blockchain can elevate tourists' experiences.
Keywords: Distributed Ledger; Technology; Environmental Impact; Thematic Analysis; Efficient